Regulation of subtelomeric fungal secondary metabolite genes by H3K4me3 regulators CclA and KdmB. Issue 3 (19th June 2019) - Lukito, Yonathan; Chujo, Tetsuya; Hale, Tracy K.; Mace, Wade; Johnson, Linda J.; Scott, Barry
Summary: Studies on the regulation of fungal secondary metabolism highlight the importance of histone H3K4 methylation regulators Set1, CclA (Ash2) and KdmB (KDM5), but it remains unclear whether these proteins act by direct modulation of H3K4me3 at the target genes. In filamentous fungi, secondary metabolite genes are frequently located near telomeres, a site where H3K4 methylation is thought to have a repressive role. Here we analyzed the role of CclA, KdmB and H3K4me3 in regulating the subtelomeric EAS and LTM cluster genes in Epichloë festucae . Depletion of H3K4me3 correlated with transcriptional activation of these genes in Δ cclA, similarly enrichment of H3K4me3 correlated with transcriptional repression of the genes in Δ kdmB which was accompanied by significant reduction in the levels of the agriculturally undesirable lolitrems. These transcriptional changes could only be explained by the alterations in H3K4me3 and not in the subtelomerically‐important marks H3K9me3/K27me3. However, H3K4me3 changes in both mutants were not confined to these regions but occurred genome‐wide, and at other subtelomeric loci there were inconsistent correlations between H3K4me3 enrichment and gene repression. Our study suggests that CclA and KdmB are crucial regulators of secondary metabolite genes, but these proteins likely act via means independent to, or in conjunction with the H3K4me3 mark. Abstract : Deletion of cclA ( ASH2 ) or kdmB ( KDM5 ) led to global reduction and accumulation of H3K4me3 that was accompanied by activation and repression of subtelomeric secondary metabolite genes respectively in the filamentous fungus Epichloë festucae . Our data suggest however that CclA and KdmB regulate these genes independently of H3K4me3.